2014
DOI: 10.1200/jco.2014.32.15_suppl.e14629
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic patterns and survival outcome of colorectal cancer in young patients: Western Saudi Arabia experience.

Abstract: Background: The prognosis of young colorectal cancer (CRC) patients has been addressed by several studies but with contradictory results. The aim of the present study was to evaluate the clinico-pathological features of young Saudi patients with CRC in addition to displaying their survival outcome. Materials and Methods: In this retrospective study, young CRC patients (≤ 40 years) diagnosed between 2007 and 2011 from 4 centres in western Saudi Arabia, were included. Clinico-pathological features, tumor markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Surgery alone is not a curative option due to mesorectal fascia invasion or regional lymphadenopathy. 3 , 4 Such stages of rectal cancer are treated with preoperative chemoradiation (CRT) followed up with curative radical surgery and adjuvant chemotherapy. This is based on recommendations from the European randomized trials that reported a reduction in the locoregional recurrence (LR) rate by 40% to 50%.…”
mentioning
confidence: 99%
“…Surgery alone is not a curative option due to mesorectal fascia invasion or regional lymphadenopathy. 3 , 4 Such stages of rectal cancer are treated with preoperative chemoradiation (CRT) followed up with curative radical surgery and adjuvant chemotherapy. This is based on recommendations from the European randomized trials that reported a reduction in the locoregional recurrence (LR) rate by 40% to 50%.…”
mentioning
confidence: 99%